2021
DOI: 10.1002/1873-3468.14171
|View full text |Cite
|
Sign up to set email alerts
|

Single‐dose immunisation with a multimerised SARS‐CoV‐2 receptor binding domain (RBD) induces an enhanced and protective response in mice

Abstract: The COVID-19 pandemic, caused by the SARS-CoV-2 coronavirus, has triggered a worldwide health emergency. Here, we show that ferritin-like Dps from hyperthermophilic Sulfolobus islandicus, covalently coupled with SARS-CoV-2 antigens via the SpyCatcher system, forms stable multivalent dodecameric vaccine nanoparticles that remain intact even after lyophilisation. Immunisation experiments in mice demonstrated that the SARS-CoV-2 receptor binding domain (RBD) coupled to Dps (RBD-S-Dps) elicited a higher antibody t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 70 publications
5
27
0
Order By: Relevance
“…Together, the combination of multiple transgenic hACE2-expressing mouse models under various promoters, adenovirus-based methods for transduction of multiple mouse strains with hACE2, mouse-adapted SARS-CoV-2 strains, and the susceptibility of mice to emerging VOC has resulted in laboratory mice becoming highly useful models for SARS-CoV-2 infection studies and efficacy testing of vaccines and therapeutics [ 220 , 221 , 222 , 223 , 224 ].…”
Section: Main Textmentioning
confidence: 99%
“…Together, the combination of multiple transgenic hACE2-expressing mouse models under various promoters, adenovirus-based methods for transduction of multiple mouse strains with hACE2, mouse-adapted SARS-CoV-2 strains, and the susceptibility of mice to emerging VOC has resulted in laboratory mice becoming highly useful models for SARS-CoV-2 infection studies and efficacy testing of vaccines and therapeutics [ 220 , 221 , 222 , 223 , 224 ].…”
Section: Main Textmentioning
confidence: 99%
“…Different cell types have been used to produce RBD antigens, such as yeast, plant, and insect cells (33,(41)(42)(43)(44). However, production in mammalian cells (12,(45)(46)(47)(48)(49) may produce an RBD antigenic domain that more closely resembles that generated during virus infection in human cells (including post-translational modifications such as glycosylation and correct folding) (50). Our results showing binding to hACE2expressing cells and the induction of neutralizing antibody titers confirm the preservation of the RBD structure and the suitable exposition of the receptor binding motif (RBM).…”
Section: Discussionmentioning
confidence: 99%
“…While RBD+alum induces significant immune responses, it has been suggested that its immunogenicity should be increased. Different approaches have been proposed to increase its immunogenicity, such as (i) expression as dimer ( 43 , 49 , 65 , 67 ) or trimers ( 45 ), (ii) fusion to carrier proteins like human IgG Fc moiety ( 44 , 67 ), tetanus toxoid ( 12 ), and interferon-α ( 67 ), (iii) addition of pan HLA-DR-binding epitope to enhance helper T cell responses ( 67 ), (iv) using nanoparticles as delivery system ( 42 , 46 , 48 , 53 , 59 ), or (v) addition of immunopotentiators as CpG ( 42 , 43 , 47 , 59 ), MPLA ( 44 ), 3M-052, or a TLR-7/8 agonist ( 45 , 59 ). Here, we demonstrated that the addition of U-Omp19 to RBD + alum formulation was able to increase the induction and breadth of SARS-CoV-2 neutralizing antibody responses, increase the frequency of RBD-specific germinal center B cells, and induce antigen-specific Th1 and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 9, 2021. ; https://doi.org/10.1101/2021.12.07.471590 doi: bioRxiv preprint Different cell types have been used to produce RBD antigens, such as yeast, plant and insect cells 32,[40][41][42][43] . However, production in mammalian cells 11,[44][45][46][47][48] may produce a RBD antigenic domain that more closely resembles that generated during virus infection in human cells (including post-translational modifications such as glycosylation and correct folding) 49 . Our results showing binding to hACE2 expressing cells and the induction of neutralizing antibody titers confirm the preservation of the RBD structure and the suitable exposition of the receptor binding motif (RBM).…”
Section: Discussionmentioning
confidence: 99%
“…While RBD+Alum induces significant immune responses, it has been suggested that its immunogenicity should be increased. Different approaches have been proposed to increase its immunogenicity, such as i) expression as dimer 42,48,65,67 or trimers 44 , ii) fusion to carrier proteins like human IgG Fc moiety 43,67 , tetanus toxoid 11 , interferon-α 67 , iii) addition of pan HLA-DR-binding epitope to enhance helper T cell responses 67 , iv) using nanoparticles as delivery system 41,45,47,52,59 or v) addition of immunopotentiators as CpG 41,42,46,59 , MPLA 43 , 3M-052 or a TLR-7/8 agonist 44,59 .…”
Section: Discussionmentioning
confidence: 99%